INFERÊNCIAS SOBRE A BIOLOGIA EVOLUTIVA DE Astyanax serratus E Astyanax laticeps (TELEOSTEI, CHARACIDAE) ATRAVÉS DE MORFOMETRIA, CITOGENÉTICA E GENÉTICA MOLECULAR COMPARADA - Schleger, Ieda Cristina (2016)
The family Characidae (Characiformes) is the most diverse in number of species among Neotropical fish. Many genera of this family, for no to present evidence of monophyly, are considered Incertae Sedis, such as Astyanax. This genus of fish groups popularly known as lambari, comprises 155 valid species. Astyanax serratus is considered endemic of the Iguaçu River, where is largely distributed. Astyanax laticeps occurs in coastal basins of the coastal region of Uruguay, south and southeast Brazil. These species are morphologically similar and are included in the complex A. scabripinnis. The purpose of this study was to determine A. serratus and A. laticeps are the same species in synonymy, or form distinct evolutionary units, but cryptic. Therefore, was used morphometric analysis, including measurements of body proportions relative to length of the body and of the head, counting number of teeth, cusps and fins. Cytogenetic analysis consisted in chromosome preparations conventional Giemsa staining, localization of constitutive heterochromatin by C-banding method, detection of nucleolar organizer regions (NORs) by impregnation with silver nitrate (Ag-NORs) and fluorescent in situ hybridization using DNA probes ribosomal (rDNA) 5S and 18S. The sequences used as DNA barcode, were obtained by partial amplification of cytochrome c oxidase I (COI) gene and the genetic distance calculated by the method of Kimura 2-parameters (K2P). The results of morphometric analysis revealed pre-jaw with two series of teeth, presence of hooks on anal and pelvic fins of males, elongated body with a humeral spot with narrow anteroventral extension in both species. Cytogenetic showed the same diploid number of 50 chromosomes, including the first pair of large metacentric chromosomes in relation to the others complements, the same karyotype formula (4m + 24sm + 6st + 16a) and even fundamental number (84). The markings of 5S rDNA coincide in the centromeric region of chromosome 19 pair and were evidenced multiple sites of 18S rDNA, located in the telomeric regions of the chromosomes in both species analyzed. The Ag-NORs showed to be coincident with 18S sites in most cases. The distribution of constitutive heterochromatin blocks occurred preferentially in the centromeric and terminals regions of chromosomes, coincident with the location of ribosomal sites and Ag-NORs in telomeric regions. The analysis of DNA barcode through the COI gene revealed an interspecific genetic divergence to 0.2%, a rate below the threshold considered for the separation of fish species (2%). These different levels of analysis suggest that A. serratus and A. laticeps are synonymous species, increasing the occurrence of A. laticeps for the Iguaçu River basin and enhancing the hypothesis of fauna sharing, caused by tectonic activities of crystalline shield. The interspecifc variations found in the mapping of constitutive heterochromatin, Ag-NORs and 18S rDNA are common in Astyanax and derived of events no robertsonian, while the differences may reflect the vicariant process, with geographic isolation of watersheds and gene flow restriction among the population of the Iguaçu River and coastal populations.